Structural change and income distribution: Accounting for regional inequality in the People's Republic of China and its changes during 1952-2012 - Guanghua Wan; Chen Wang; Xun Zhang (Asian Development Bank Institute (ADBI), 2016)
This study explores the relationship between inequality and structural transformation by constructing a theoretical model, developing analytical frameworks, and implementing a case study. The general equilibrium model we develop demonstrates that inequality exhibits an inverted U shape as structural change proceeds from onset to completion. Our analytical frameworks enable decomposition of total inequality into sector contributions and a change in total inequality into a component attributable to structural transformation and the other component to concentration or spatial agglomeration. Applying the decomposition frameworks to data from the People's Republic of China yield various interesting findings and more importantly confirms the inverted U shape as predicted by our theoretical model.
Keywords: D63; O53; R12; O18; 330; Structural transformation; structural change; income distribution; income inequality; inequality decomposition; spatial agglomeration; macroeconomics; China